Mistral's Daughter - Krantz, Judith (New York Bantam Books, 1983)
They were three generations of magnificent red-haired beauties born to scandal, bred to success, bound to a single extraordinary man--Julien Mistral, the painter, the genius, the lover whose passions had seared them all. Maggy--Flamboyant mistress of Mistral's youth, the toast of Paris in the '20s. Her luminous flesh was immortalized in the paintings that made Mistral legendary. Teddy--Maggy's daughter, the incomparable cover girl who lived fast and left as her legacy Mistral's dazzling love child. Fauve--Mistral's daughter, the headstrong, fearless glory girl whose one dark secret drove her to rule the world of high fashion and to risk everything in a feverish search for love. From the '20s Paris of Chanel, Colette, Picasso and Matisse to New York's sizzling new modeling agencies of the '50s, to the model ward of the '70s, Mistral's Daughter captures the explosive glamour of life at the top of the worlds of art and high fashion. Judith Krantz has given us a glittering international tale as spellbinding as her other celebrated best-sellers, Scruples, Princess Daisy, I'll Take Manhattan, Till We Meet Again, Scruple s Two, Dazzle, and Lovers.
Follows three generations of Lunel women--and their involvement with the driven artist Julien Mistral--from Paris in the 1920s to the world of American high fashion.
Keywords: Romance Fiction -- Artists